PENERAPAN PENDEKATAN CONTEXTUAL TEACHING LEARNING (CTL) BERBANTUAN LEMBAR KERJA SISWA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI MIPA 2 SMAN 6 MERANGIN - Sufriati, S.Pd (Pendidikan Matematika | STKIP YM Bangko, 2021)
The purpose of this study was to determine the increase in students' learning motivation by applying Contextual Teaching and Learning (CTL) to physics learning carried out in class XI MIPA 2 at State Senior High School 6 Merangin. This type of research is classroom action research (CAR) using a cycle model that includes 4 stages, namely planning, action, observation and reflection. The four stages are cycles that take place repeatedly and are carried out with the same steps and are focused on students of class XI MIPA 2 using Contextual Teaching and Learning (CTLlearning). Based on the results of research that has been done, it shows that the results of student learning motivation have increased. This increase can be seen through the cycles that have been carried out. In the first cycle the percentage of indicators of student learning motivation is 59.51% included in the low category. In the second cycle, it increased to 66.92% which is still in the low category. In the third cycle, it increased to 78.47%, this means that the average percentage of indicators of student learning motivation has exceeded the criteria for the success of the action set, which is 70%.